ANALISIS KINERJA PENYULUH PERTANIAN DI KECAMATAN SELUMA SELATAN KABUPATEN SELUMA (Ditinjau dari Aspek Tangible dan Aspek Reabilitas dalam Kegiatan Penyuluhan Pertanian) - Noviyanto, Hernowo; Arjianto, Arjianto; Dani, Rahiman; Aprianty, Henny; Parwito, Parwito (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
The purpose of this study was to describe the activities of agricultural consultants in increasing agricultural production in South Seluma District, Seluma Regency in terms of concrete aspects and reliable aspects using a qualitative descriptive approach. Data collection methods include interviews, observation, and collection. From the results of the study, it can be concluded that agricultural extension activities in improving the physical appearance of crops (Tangibel) include aspects of the facilities used by agricultural extension workers which are quite good or help produce new plants in the sense of. from reliable information. Agricultural Extension for each member of the Farmer Group. In this indicator, agricultural extension workers are quite capable of providing reliable service by providing new information, being responsible and implementing it when the information is in the form of a government contract or program, and increasing the institutional capacity of farmer groups, economic institutions, and agricultural support. Economic actors build partnerships.